2007
DOI: 10.1097/scs.0b013e31803fdff7
|View full text |Cite
|
Sign up to set email alerts
|

Struggling With Ischemia Reperfusion Injury

Abstract: Ischemia reperfusion (I/R) injury is a complicated injury that compels either the patient or the practitioner. In the literature, there still is a debate over how to manage the injury. Typically, no single treatment is feasible. So far, numerous substances have been used as treatments and the majority of these are antioxidants. In this article, a combined therapy is implemented for a patient suffering from I/R injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Also, vitamin E and iloprost (synthetic analog of prostacyclin PGI 2 ) combination demonstrated that they attenuate reperfusion injury more efficiently than their separate use, in skeletal muscle I/R injury model [68]. In addition to these, Kayiran et al [69] showed that combined usage of vitamins C, E, acetylcysteine, and prednisolone alleviated the results of ischemia and enhanced the flap survival on free radial forearm flap. There is a wide range use of substances in the literature to prevent I/R injury, but there is no single ideal drug that can overcome this damage; so, we think that the use of combined therapy is more successful in achieving impressive results.…”
Section: Discussionmentioning
confidence: 99%
“…Also, vitamin E and iloprost (synthetic analog of prostacyclin PGI 2 ) combination demonstrated that they attenuate reperfusion injury more efficiently than their separate use, in skeletal muscle I/R injury model [68]. In addition to these, Kayiran et al [69] showed that combined usage of vitamins C, E, acetylcysteine, and prednisolone alleviated the results of ischemia and enhanced the flap survival on free radial forearm flap. There is a wide range use of substances in the literature to prevent I/R injury, but there is no single ideal drug that can overcome this damage; so, we think that the use of combined therapy is more successful in achieving impressive results.…”
Section: Discussionmentioning
confidence: 99%
“…The palatal periosteum and flap should be maintained for maximum blood supply to the segmented bone, which is the most important factor [72], so that the bone is not devitalized as a result of ischemia after the bone is detached from its blood supply [73]. The use of piezoelectric device contributes for precise control of the osteotomy to reduce trauma to the soft tissue.…”
Section: Second Stage Surgerymentioning
confidence: 99%